MANAJEMEN PENGEMBANGAN KEBIJAKAN WISATA BAHARI DI KAWASAN EKONOMI KHUSUS MANDALIKA LOMBOK TENGAH: STUDI KASUS PANTAI KUTA - Rahmatika, Alghisna; Kusumastanto, Tridoyo; Sadelie, Agus (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
This study aims to estimate the condition of economic value and demand of this particular area, estimate the carrying capacity as a condition of supply and formulate a strategy to determine the policy of marine tourism development with considerations of sustainability of this Kuta Beach Area using a dynamic model. The method used for gathering the necessary data is purposive sampling, while the method of data analysis is the analysis of supply with a carrying capacity analysis approach, analysis of tourism demand with Travel Cost Method (TCM), financial feasibility analysis, prospective analysis and dynamic analysis. The result of this research shows the number of tourists in Kuta Beach is less than the carrying capacity of the island, so there is an opportunity to increase the number of tourists. The result of demand analysis based on TCM is Rp 8.614.874.595/year with an average of consumer surplus of Rp 42.250 with a number of 203.899 Ã‚Â tourists in 2015. Based on the financial feasibility analysis such as NPV, Net B/C, and IRR, it is concluded that the business of tourism in Kuta Beach is both financially and economically feasible. The prospective analysis recommends a policy based on the opinion of the stakeholders that can be formulated as strategic implications and anticipatory actions in the Kuta Beach Area management plan. Dynamic analysis shows an increase in ecological, economic and social submodels.